Establishment of a superinfection exclusion method for pestivirus titration using a recombinant reporter pestiviruses - MIMURA, Yume; HIONO, Takahiro; HUYNH, Loc Tan; OGINO, Saho; KOBAYASHI, Maya; ISODA, Norikazu; SAKODA, Yoshihiro (Journal of Veterinary Medical Science, 2024)
Pestiviruses are classified into two biotypes based on their cytopathogenicity. As the majority of pestivirus field isolates are noncytopathogenic, their titration requires alternative methods rather than direct observation of cytopathogenic effects, such as immunostaining using specific antibodies or interference with cytopathogenic strains. However, these methods require microscopic observation to assess virus growth, which is time- and labor-intensive, especially when handling several samples. In this study, we developed a novel luciferase-based pestivirus titration method using the superinfection exclusion phenomenon with recombinant reporter pestiviruses that possessed an 11-amino-acid subunit derived from NanoLuc luciferase (HiBiT). In this method, swine kidney cells were inoculated with classical swine fever virus (CSFV) and superinfected with the reporter CSFV vGPE−/HiBiT 5 days postinoculation. Virus titer was determined based on virus growth measured in luminescence using the culture fluid 3 days after superinfection; the resultant virus titer was comparable to that obtained by immunoperoxidase staining. Furthermore, this method has proven to be applicable for the titration of border disease virus (BDV) by superinfection with both the homologous reporter BDV and heterologous reporter CSFV, suggesting that this novel virus titration method is a simple technique for automated virus detection based on the luciferase system.